(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
Continuing previous similar research, the ability of sulfates of elements of the second group – magnesium, calcium and zinc, to produce peroxosolvates, the methods for their preparation, as well as their properties have been studied. It has been shown that these sulfates are able to produce peroxosolvates with different molar ratios: MgSO4‧H2O2, CaSO4‧0.04H2O2, ZnSO4‧0.05H2O2. The authenticity, composition and nature of the obtained peroxosolvates have been elucidated by the methods of X-ray and IR spectroscopy. Quantitative data on the decomposition of hydrogen peroxide in dry peroxosolvates of magnesium and zinc sulfates were calculated.